Gender Differences in the Toxicokinetics of Triptolide after Single- and Multiple-dose Administration in Rats - Liu, L.; Zhang, J.; Wang, Z.; Xu, D.; Jiang, Z.; Wang, T.; Ju, W.; Zhang, L. (Drug Research, 2015)
Triptolide is a natural compound extracted from the traditional Chinese medicine Tripterygium wilfordii Hook F with distinguishing pharmacological activities and evident toxicities. We reported previously that 28 continuous days of oral administration of triptolide in rats resulted in gender dimorphic profiles in toxicities. To better understand this issue, the toxicokinetics of triptolide was observed in this study. Rats of both sexes were administered 400 μg/kg triptolide either as a single dose or multiple doses for 28 days. Triptolide concentrations in rat plasma were determined using high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS). The plasma concentration-time curve and toxicokinetic parameters revealed gender differences after single and repeated triptolide administration, including significantly higher area under the plasma concentration-time curve (AUC0–∞) and peak plasma concentration (Cmax), lower clearance rate (CL) and longer terminal elimination half-life (t1/2) of triptolide in females, and lower drug exposure levels and greater CL in males. The gender differential disposition of triptolide may be the cause of increased toxicity in females. Moreover, auto-inhibition of metabolism and the resulting increase in drug exposure were observed after repeated dosing. The AUC0–∞ of triptolide was increased 6-fold in females and 2-fold in males, while the CL of triptolide was significantly decreased by 84% in females and 55% in males. These results indicated that gender-related differences existed in the toxicokinetics of triptolide and long-term oral administration of triptolide resulted in drug accumulation, which might account for the gender differences in the toxicities of triptolide.
Keywords: gender difference; triptolide; toxicokinetics